(untitled) (Scientiae Studia, 2011)
In this article, I characterize the concept of visual evidence as a particular kind of evidence in which counterfactual conditions analogous to those met by perception are present. I argue that visual evidence can also be produced by scientific instruments, such as various kinds of microscopes for which we know that the relevant conditions are, in fact, satisfied. Thus, both perception and the information generated by instruments that yield visual evidence share the same epistemic properties. Drawing on this fact, I finally offer a way of extending the observable beyond instances of unaided perception, but which still preserves, within an empiricist view, cases in which certain objects cannot be observed.